2016
DOI: 10.3389/fpsyg.2016.02037
|View full text |Cite
|
Sign up to set email alerts
|

Trustworthy Tricksters: Violating a Negative Social Expectation Affects Source Memory and Person Perception When Fear of Exploitation Is High

Abstract: People who are high in victim-sensitivity—a personality trait characterized by a strong fear of being exploited by others—are more likely to attend to social cues associated with untrustworthiness rather than to cues associated with trustworthiness compared with people who are low in victim-sensitivity. But how do these people react when an initial expectation regarding a target’s trustworthiness turns out to be false? Results from two studies show that victim-sensitive compared with victim-insensitive individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 35 publications
0
13
1
Order By: Relevance
“…Some studies suggest that this is doable: For instance, Süssenbach and Gollwitzer (2015; Study 2) and Süssenbach et al. (2016; Study 2) manipulated the risk of being exploited experimentally and showed that victim‐sensitive individuals reacted more strongly to such a manipulation than victim‐insensitive individuals. Such a manipulation could be used in future studies to test the hypothesis that VS‐Max causally affects group outcomes more rigidly.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest that this is doable: For instance, Süssenbach and Gollwitzer (2015; Study 2) and Süssenbach et al. (2016; Study 2) manipulated the risk of being exploited experimentally and showed that victim‐sensitive individuals reacted more strongly to such a manipulation than victim‐insensitive individuals. Such a manipulation could be used in future studies to test the hypothesis that VS‐Max causally affects group outcomes more rigidly.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, financial advisers could help themselves and the wider population by performing periodic evaluations of FPR to identify changes in savings trends over time and achieve a better understanding of their clients as a basis for the design of individual FPR proposals tailored to individual needs, given the relevance of personal priorities and the meanings individuals attach to goals on levels of FPR engagement (Süssenbach, Gollwitzer, Mieth, Buchner, & Bell, 2016). Finally, it has been argued that the motivational processes underlying financial behavior in general, and specifically FPR practices, are crucial to achieving the desired outcomes (Martínez-Ruiz, Izquierdo-Yusta, Olarte-Pascual, & Reinares-Lara, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with previous studies, Christian identity, economically motivated identity, and trust in the 3 PSA sources were measured with single-item 7-point Likert scales [ 41 - 43 ]. Identity-framed PSAs were deemed to be aligned with the participant’s identity when the participant’s identity scores were 6 or 7 and the participant did not distrust the source (ie, trust in the source was ≥4).…”
Section: Methodsmentioning
confidence: 99%